Techno-Economic Evaluation of a Bagasse Gasification Biomass Power Plant in the Sugar Industry - DIMAS SURYA FIRMANSYAH; ROYB FATKHUR RIZAL; MISBAHUL MUNIR (Institut Teknologi Nasional, Bandung, 2026)
Bagasse utilization for power generation in sugar mills remains dominated by inefficient conventional boilers. This study assesses economic feasibility of a hybrid bagasse gasification power system using HOMER Pro software. The model includes a biomass gasifier, diesel generator, and grid connection, using operational data from Krebet Sugar Factory. Four sensitivity scenarios examined variations in investment cost, operational cost, and biomass price. The hybrid system yields a Net Present Cost of 14.2 million USD and Levelized Cost of Electricity of 0.088 USD/kWh, substantially outperforming the existing system with NPC 21.1 million USD and LCOE 0.203 USD/kWh. Investment viability is supported by an Internal Rate of Return of 12% and payback period of 4.8 years. Sensitivity analysis verifies economic resilience despite 20% cost escalation and elevated biomass prices.